Advanced glycation end products induce brain-derived neurotrophic factor release from human platelets through the Src-family kinase activation. Issue 1 (December 2017) - Furukawa, Kazuo; Fuse, Ichiro; Iwakura, Yuriko; Sotoyama, Hidekazu; Hanyu, Osamu; Nawa, Hiroyuki; Sone, Hirohito; Takei, Nobuyuki
Abstract Background Brain-derived neurotrophic factor (BDNF) exerts beneficial effects not only on diabetic neuropathies but also on cardiovascular injury. There is argument regarding the levels of serum BDNF in patients with diabetes mellitus (DM). Because BDNF in peripheral blood is rich in platelets, this may represent dysregulation of BDNF release from platelets. Here we focused on advanced glycation end products (AGEs), which are elevated in patients with DM and have adverse effects on cardiovascular functions. The aim of this study is to elucidate the role of AGEs in the regulation of BDNF release from human platelets. Methods Platelets collected from peripheral blood of healthy volunteers were incubated with various concentrations of AGE (glycated-BSA) at 37 °C for 5 min with or without BAPTA-AM, a cell permeable Ca2+ chelator, or PP2, a potent inhibitor of Src family kinases (SFKs). Released and cellular BDNF were measured by ELISA and calculated. Phosphorylation of Src and Syk, a downstream kinase of SFKs, in stimulated platelets was examined by Western blotting and immunoprecipitation. Results AGE induced BDNF release from human platelets in a dose-dependent manner, which was dependent on intracellular Ca2+ and SFKs. We found that AGE induced phosphorylation of Src and Syk. Conclusions AGE induces BDNF release from human platelets through the activation of the Src-Syk-(possibly phospholipase C)-Ca2+ pathway. Considering the toxic action of AGEs and the protective roles of BDNF, it can be hypothesized that AGE-induced BDNF release is a biological defense system in the early phase of diabetes. Chronic elevation of AGEs may induce depletion or downregulation of BDNF in platelets during the progression of DM.